Factors affecting treatment seeking patterns among public in three selected areas in Kuantan - Mat Yusof, Afzan; Md Isa, Muhammad Lokman (2016)
Seeking for treatment is a vital step to be done when an individual gets sick. However, due to certain circumstances people do not able to seek for treatment. This study aims to identify the factors affecting treatment seeking patterns among public in three selected areas in Kuantan, to explore factors affecting people not able or avoid to seek for treatment and to determine the relationship between treatment seeking patterns and the influential factors (distance and accessibility and behaviors; attitude to health and health care and self perception). A cross sectional survey was done at Taman Gelora, Teluk Cempedak and Terminal Makmur, Kuantan, Pahang. Convenient sampling method was used in this study. 201 respondents involved in this study and semi-structured questionnaire modified from Adamson et al. (2003). Results showed that data was normally distributed to male (50.2%) and female (49.8%) according to gender. Gen Y (16-26 years old) was the highest proportion of respondents (58.7%) in this study. Majority of the respondents had neutral attitude to health and health care (94.03%) and also to self perception (73.63%). From the results, there were significant association between distance and accessibility and monthly income (p = 0.012) plus between self perception and demographic data (p = 0.026, p = 0.009, p < 0.001). Self perception was statistically the most influencing factor people not able to seek for treatment. As conclusion, the findings identified the most common influencing factors people not able to seek for treatment and could be used to urge the government to ensure equal distribution of healthcare services throughout the country.